Functional Macromolecule‐Enabled Colloidal Synthesis: From Nanoparticle Engineering to Multifunctionality. Issue 44 (29th August 2019) - Lu, Derong; Zhou, Jiajing; Hou, Shuai; Xiong, Qirong; Chen, Yonghao; Pu, Kanyi; Ren, Jinghua; Duan, Hongwei
Abstract: The synthesis of well‐defined inorganic colloidal nanostructures using functional macromolecules is an enabling technology that offers the possibility of fine‐tuning the physicochemical properties of nanomaterials and has contributed to a broad range of practical applications. The utilization of functional reactive polymers and their colloidal assemblies leads to a high level of control over structural parameters of inorganic nanoparticles that are not easily accessible by conventional methods based on small‐molecule ligands. Recent advances in polymerization techniques for synthetic polymers and newly exploited functions of natural biomacromolecules have opened up new avenues to monodisperse and multifunctional nanostructures consisting of integrated components with distinct chemistries but complementary properties. Here, the evolution of colloidal synthesis of inorganic nanoparticles is revisited. Then, the new developments of colloidal synthesis enabled by functional macromolecules and practical applications associated with the resulting optical, catalytic, and structural properties of colloidal nanostructures are summarized. Finally, a perspective on new and promising pathways to novel colloidal nanostructures built upon the continuous development of polymer chemistry, colloidal science, and nanochemistry is provided. Abstract : Functional macromolecules provide tremendous synthetic opportunities and flexibility to construct well‐defined inorganic nanomaterials that are not accessible by conventional colloidal synthesis based on small‐molecular ligands. The utilization of functional polymers in colloidal synthesis makes it possible to translate the intrinsic properties of polymers to structural parameters of inorganic constructs at a nanoscale precision.